Cultural, Social, Religious Beliefs and Practices During Postpartum Period Among Post Natal Women in Selected Rural and Urban Health Care Settings - Ananya Bhakta; Smritikana Mani (Indonesian Journal of Global Health Research, 2019)
Belief is the state of mind in which a person thinks something to be the case, with or without there being empirical evidence to prove that something is the case with factual certainty. In developing countries, over 60% of maternal deaths occur during the postpartum period. This period is also greatly influenced by different types of socio-cultural beliefs & practices that increases the risk for poor maternal and child health. A study was conducted to identify and analyse the cultural, social, religious beliefs and practices during postpartum period among postnatal women in Erashal BPHC & Medical College & Hospital of West Bengal. A comparative survey design was adopted in this study. A non probability purposive sampling technique was used to select 120 postnatal women from rural Erashal BPHC & 160 from urban Medical college & hospital as study subject. A valid & reliable Structured Interview schedule(r-0.85,0.90)was used to collect data from the postnatal women who were admitted for delivery and staying postnatal ward. The findings showed that the harmful beliefs regarding maternal, baby care, breast feeding & family planning aspect were present among women during postpartum period(R-75%,U-54%) Harm less beliefs regarding maternal care& breast feeding aspect were present in postpartum period(R-31% U-42 %). Beneficial beliefs regarding separation aspect were present in postpartum period(R-79%,U-90%).The practices were seen in post partum period(R-52%,U-21%).There was a significant difference in belief among rural & urban women as evidenced by ‘t’ test(t-11.38 at df 278 at p<0.05) . There was a significant difference in practice among rural& urban women (t-6.85 at df278 at 0.05 level).Significant relationship(r-0.35 , 0.28 at p<0.05) was seen between beliefs &practices during postpartum period in both area. There was a significant association (χ2-5.36, 10.56 at p<0.05) between religion with beliefs in both area. The significant association was seen between family type with beliefs in rural (χ2-4.41 at p<0.05) but not in urban. The study concluded that, a concerned matter of issue can be raised to prevent the practices contrary with harmful beliefs by counselling and evaluation of views of the mothers during reproductive period. Keywords: beliefs and practices, postpartum period, postnatal women, rural and urban settings